Bioethics and the Framing of Climate Change's Health Risks. (3rd September 2014) - Valles, Sean A.
Abstract Cheryl Cox MacPherson recently argued, in an article for this journal, that 'Climate Change is a Bioethics Problem'. This article elaborates on that position, particularly highlighting bioethicists' potential ability to help reframe the current climate change discourse to give more attention to its health risks. This reframing process is especially important because of the looming problem of climate change skepticism. Recent empirical evidence from science framing experiments indicates that the public reacts especially positively to climate change messages framed in public health terms, and bioethicists are particularly well positioned to contribute their expertise to the process of carefully developing and communicating such messages. Additionally, as climate framing research and practice continue, it will be important for bioethicists to contribute to the creation of that project's nascent ethical standards. The discourse surrounding antibiotic resistance is posited as an example that can lend insight into how communicating a public health‐framed message, including the participation of bioethicists, can help to override public skepticism about the findings of politically contentious scientific fields.